2012
DOI: 10.1073/pnas.1216398109
|View full text |Cite
|
Sign up to set email alerts
|

Candidate autism gene screen identifies critical role for cell-adhesion molecule CASPR2 in dendritic arborization and spine development

Abstract: Mutations in the contactin-associated protein 2 (CNTNAP2) gene encoding CASPR2, a neurexin-related cell-adhesion molecule, predispose to autism, but the function of CASPR2 in neural circuit assembly remains largely unknown. In a knockdown survey of autism candidate genes, we found that CASPR2 is required for normal development of neural networks. RNAi-mediated knockdown of CASPR2 produced a cell-autonomous decrease in dendritic arborization and spine development in pyramidal neurons, leading to a global declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(203 citation statements)
references
References 45 publications
4
197
2
Order By: Relevance
“…The marker showing the strongest association with sustained attention/vigilance, which surpassed genome‐wide significance cut‐off, is of potential interest since it is located within a brain expressed gene ( CNTNAP5 ) previously implicated in neuropsychiatric diseases with known disturbances in sustained attention, that is bipolar disorder, autism and attention‐deficit hyperactivity disorder [Djurovic S et al, 2010; Pagnamenta AT et al, 2010; Neale BM et al, 2010 ] . CNTNAP5 protein belongs to the neurexin superfamily of cell‐adhesion molecules, which have been shown to constitute key regulators of synapse formation and neurotransmission [Anderson GR et al, 2012; Karayannis T et al, 2014]. Suggestive evidence of association was observed for three additional loci, located within genes whose protein products are involved in glutamatergic signaling ( GRIK3 ) and synaptic vesicle trafficking processes ( ERC2 , BIN1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The marker showing the strongest association with sustained attention/vigilance, which surpassed genome‐wide significance cut‐off, is of potential interest since it is located within a brain expressed gene ( CNTNAP5 ) previously implicated in neuropsychiatric diseases with known disturbances in sustained attention, that is bipolar disorder, autism and attention‐deficit hyperactivity disorder [Djurovic S et al, 2010; Pagnamenta AT et al, 2010; Neale BM et al, 2010 ] . CNTNAP5 protein belongs to the neurexin superfamily of cell‐adhesion molecules, which have been shown to constitute key regulators of synapse formation and neurotransmission [Anderson GR et al, 2012; Karayannis T et al, 2014]. Suggestive evidence of association was observed for three additional loci, located within genes whose protein products are involved in glutamatergic signaling ( GRIK3 ) and synaptic vesicle trafficking processes ( ERC2 , BIN1 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, in neuronal cultures, transient Caspr2 knockdown produced decreased amplitude (but not frequency) of synaptic responses, suggesting a cell-autonomous impairment of synaptic transmission. 68 However, in a mouse model of Caspr2 loss, firing rate and amplitude were not affected. Instead, a reduction of synchronicity of neuronal firing in the somatosensory cortex was detected.…”
Section: Caspr2 and Neuronal Networkmentioning
confidence: 95%
“…CASPR2 knockdown causes decreased dendritic arborisation in mouse cortical neurons, 68 suggesting a normal role in promoting outgrowth and connectivity. Axonal pathfinding defects were also observed when Nrx-IV was absent from Drosophila embryos.…”
Section: Caspr2 and Neuronal Networkmentioning
confidence: 99%
“…However, CNTNAP2 is also abundant in the brain, where it is enriched in the synaptic plasma membrane fraction (14). Notably, a recent article reported that shRNA-mediated knockdown of CNTNAP2 in young developing cultured cortical neurons causes a significant and cell-autonomous reduction of AMPA and NMDA mEPSCs (miniature excitatory postsynaptic currents) and GABA mIPSCs (miniature inhibitory postsynaptic currents), without affecting presynaptic function (35). Knockdown also resulted in reduced dendritic arborization and reduced spine head size, but not spine density.…”
Section: Significancementioning
confidence: 99%
“…Because CNTNAP2 is at excitatory synapses, and Anderson et al (35) have shown that it regulates synapse development, we wanted to see whether it has synaptogenic properties. We used a coculture assay in which we expressed tagged CNTNAP2 constructs in HEK293 cells, which we then cocultured with hippocampal neurons.…”
Section: Cntnap2 Is Dispensable For Synapse Formation and Axon Andmentioning
confidence: 99%